Pemanfaatan IoT (Internet of Things) Dalam Monitoring Kadar Kepekatan Asap dan Kendali Camera Tracking - Abdullah Abdullah; Cholish Cholish; Moh Zainul Haq (PTE FTK UIN Ar-Raniry, 2021)
Research has been carried out on the use of the Internet of Things in smoke density levels monitoring and camera movement control. Internet of Things as long distance communication for monitoring and control systems. In this research, the system can detect smoke levels and can monitor it via an android phone, besides this system is equipped with camera movement control so that the camera position can be controlled remotely to be positioned towards the center/source where smoke is detected, so this system is needed as building and industry security as a fire prevention. This study uses a smoke density detection sensor type MQ-2, Arduino Uno as a controller, Esp8266 as a Wifi module and a servo motor as a camera driver. The results of the tests that have been carried out prove that the system has been successfully integrated and works according to the target, which is to detect the concentration of smoke and monitor remotely via an android phone and camera movement control properly.